2013
DOI: 10.1111/jopr.12075
|View full text |Cite
|
Sign up to set email alerts
|

An In Vitro Comparison of Shear Bond Strength of Zirconia to Enamel Using Different Surface Treatments

Abstract: Airborne-particle abrasion followed by the application of a zirconia primer produced the highest bond strength to enamel. Therefore, it can be recommended as a promising surface treatment method to achieve a durable bond to densely sintered zirconia ceramics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
1
11

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 39 publications
5
38
1
11
Order By: Relevance
“…In fact, a definitive cementation protocol for high strength ceramics has not been validated yet; sandblasting of the inner side of zirconia has been suggested in the literature to increase surface roughness and promote micromechanical interlocking [18]. Different air-blasting protocols associated with chemical primers (i.e., formulations containing MDP molecules or silane coupling agents) are the most recommended conditioning methods for zirconia restorations [15, 23]; however, some studies have shown that bond strength might decrease over time due to aging of the interface and lead to failure [24]. …”
Section: Discussionmentioning
confidence: 99%
“…In fact, a definitive cementation protocol for high strength ceramics has not been validated yet; sandblasting of the inner side of zirconia has been suggested in the literature to increase surface roughness and promote micromechanical interlocking [18]. Different air-blasting protocols associated with chemical primers (i.e., formulations containing MDP molecules or silane coupling agents) are the most recommended conditioning methods for zirconia restorations [15, 23]; however, some studies have shown that bond strength might decrease over time due to aging of the interface and lead to failure [24]. …”
Section: Discussionmentioning
confidence: 99%
“…Os autores concluíram que o jateamento com partículas de óxido de alumínio seguido da aplicação de um primer para zircônia alcançou o melhor resultado de união. Da mesma forma, Zandparsa et al 19 observaram que o jateamento seguido da aplicação de um primer (Z-PRIME Plus -Bisco, Inc., Schaumburg, IL) produziu uma maior força de união, capaz de resistir à degradação ao longo do tempo. Além disso, os autores salientam que a zircônia tratada com o jateamento apresenta uma ligação comparável àquela obtida entre o cimento resinoso e o esmalte.…”
Section: Revisão Da Literatura/discussãounclassified
“…Autorzy podają, że polepszenie połączenia między kompozytem a powierzchnią tlenku cyrkonu wystę-puje po wcześniejszym zastosowaniu: piaskowania tlenkiem glinu (36,37), lasera Er:YAG (38), trawienia na gorąco (35), piaskowania oraz nałożeniu primera zawierającego monomery fosforanowe (16,(39)(40)(41). Piaskowanie powierzchni tlenku cyrkonu może jednak mieć skutki uboczne w postaci powstawania mikropęknięć, szczelin i zmian strukturalnych (33).…”
Section: T H I S C O P Y I S F O R P E R S O N a L U S E O N L Y -D Iunclassified